Deletion of PPARα in mouse brown adipocytes increases their De Novo Lipogenesis - Pierre-Louis Batrow; Sylvie Caspar-Bauguil; Nathalie Rochet; Nadine Gautier; Anne-Sophie Rousseau; Marielle Maret; Samah Rekima; Etienne Mouisel; Emmanuel Van Obberghen; Christian H. Roux; Hervé Guillou; Catherine Postic; et al. (Molecular Metabolism)
Objective: Peroxisome Proliferator-Activated Receptors (PPARs) are nuclear receptors involved in the control of lipid metabolism. The PPARα isoform is highly expressed in brown adipose tissue (BAT). However, its precise role in BAT remains unclear. Here, we aimed to investigate the role of PPARα in BAT of high fat diet-induced obese mice in a thermoneutral environment. Methods: We used tamoxifen-inducible-BAT specific PPARα knockout mice (PPARαBATKO) that were housed at thermoneutrality to minimize BAT basal activation, fed a high-fat diet for 20 weeks and challenged with a β3-adrenergic agonist (CL316,243) during the last week. Both male and female mice were studied. Results: Body weight and glucose tolerance tests were similar in both sexes and genotypes. However, BAT morphology was altered in PPARαBATKO mice, with more unilocular and larger lipid droplets compared to control mice, suggesting BAT impaired function. Indeed, when treated with CL316,243, both male and female mice had increased De Novo Lipogenesis (DNL), reflected by an increased expression of ChREBPβ and lipogenic enzymes ACLY, ACC1, FASN and SCD1. These changes were accompanied by an increase in fatty acids in triglycerides, and thus an increase in lipid storage. Moreover, lipid profiles in phospholipids were different, suggesting a modification in the membrane content with an increase of palmitoleate. Conclusions: Altogether, our results reveal a key role for PPARα in DNL in BAT and in the regulation of lipid metabolism in HFD-induced obesity.